Sinergi AI dalam Literasi Akademik: Eksplorasi Grammarly dan ChatGPT dalam Penguatan Struktur dan Gaya Bahasa Teks Persuasif Mahasiswa - Nurhusna, Nurhusna; Shafariana, Shafariana; Herdiani, Rizki (PPJB-SIP (Perkumpulan Pengelola Jurnal Bahasa dan Sastra Indonesia serta Pengajarannya)., 2025)
This study aims to analyze the effectiveness of the synergy between Grammarly and ChatGPT in improving students’ persuasive writing skills, particularly in terms of argumentative structure and stylistic expression. The research is grounded in the current challenge of academic literacy in the era of artificial intelligence (AI), which requires students not only to write with linguistic accuracy but also to convey ideas persuasively and coherently. A mixed-method approach was employed through a quasi-experimental design combined with a perception survey. The participants consisted of 56 students from a language education program who engaged in AI-assisted writing instruction. Quantitative data were obtained from pretest and posttest writing assessments, while qualitative data were collected through open-ended questionnaires and reflective interviews. Data analysis involved paired-sample t-tests and thematic analysis. The findings revealed a significant improvement in students’ writing performance after utilizing Grammarly and ChatGPT. The average score for structural organization increased from 71.0 to 81.7, while the stylistic aspect improved from 69.3 to 81.9. Students reported that Grammarly helped them identify and correct linguistic errors and enhance their language awareness, whereas ChatGPT supported idea generation, argument development, and rhetorical variation. The synergy between these tools fostered a more reflective and self-regulated writing process, consistent with the theoretical frameworks of AI-mediated learning and social constructivism. Theoretically, this research reinforces the concepts of formative feedback and Cognitive Apprenticeship in academic writing instruction. Pedagogically, the findings indicate that integrating AI technology can serve as an innovative strategy for teaching writing, provided that it is accompanied by ethical guidance and reflective supervision from instructors. Thus, the synergy between Grammarly and ChatGPT not only enhances students’ writing quality but also transforms the way they learn to write critically, creatively, and responsibly in the digital literacy era.